Determination of the appropriate propofol infusion rate for outpatient upper gastrointestinal endoscopy-a randomized prospective study. Issue 1 (December 2016) - Li, Qiongzhen; Zhou, Qinghe; Xiao, Wangpin; Zhou, Hongmei
Abstract Background Pain and discomfort related to endoscopy sessions can be alleviated by sedation, which minimizes anxiety and allows safe examination. For outpatient endoscopy, reliable short-term sedation without secondary effects is required. This study aimed to assess the effects of intravenous propofol rates on sedation in outpatients undergoing upper gastrointestinal endoscopy. Methods This randomized prospective study evaluated 300 outpatients submitted to upper gastrointestinal endoscopy. Patients received propofol at 500, 1000 or 2000 ml/h. The primary outcome assessed was hypoxemia incidence. In addition, time to sedation and incidence of hypotension, deep sedation, extremity motor activity, cough, nausea, hiccough, and awareness were evaluated. Results Recovery time and incidence of hypoxemia, hypotension, and deep sedation were significantly increased in individuals treated at 2000 ml/h in comparison with values obtained for 500 and 1000 ml/h groups (P < 0.01). Compared with the 500 ml/h group, motor activity of the extremities, cough, nausea, hiccough, and awareness were significantly decreased and the mean scores for endoscopist's and patients' satisfaction were significantly increased in the 1000 and 2000 ml/h groups (P < 0.01). Conclusion Propofol infused at 1000 ml/h appeared to be the most suitable infusion rate for outpatient upper gastrointestinal endoscopy. Trial registration Registration number:ChiCTR-TRC-14004786 ; Registration date: 2014-06-04